More-than-Moore 2.5D and 3D SiP integration - Radojcic, Riko (Springer, 2017)
This book presents a realistic and a holistic review of the microelectronic and semiconductor technology options in the post Moore?s Law regime. Technical tradeoffs, from architecture down to manufacturing processes, associated with the 2.5D and 3D integration technologies, as well as the business and product management considerations encountered when faced by disruptive technology options, are presented. Coverage includes a discussion of Integrated Device Manufacturer (IDM) vs Fabless, vs Foundry, and Outsourced Assembly and Test (OSAT) barriers to implementation of disruptive technology options. This book is a must-read for any IC product team that is considering getting off the Moore?s Law track, and leveraging some of the More-than-Moore technology options for their next microelectronic product.